Thermal plasma of electric arc discharge in air between composite Cu-C electrodes - Veklich, A.; Fesenko, S.; Boretskij, V.; Cressault, Y.; Gleizes, A.; Teulet, Ph.; Bondarenko, Y.; Kryachko, L. (Вопросы атомной науки и техники, 2014)
The complex technique of plasma property studies is suggested. As the first step the radial profiles of temperature and electron density in plasma of free burning electric arc discharge in air between Cu-C composite and brass electrodes, as well as copper electrodes in air flow, were measured by optical emission spectroscopy techniques. As the next step the radial profiles of electric conductivity of plasma mixture were calculated by solution of energy balance equation. The electron density is obtained from electric conductivity by calculation in assumption of local thermodynamical equilibrium in plasma. Предложена комплексная методика исследования плазмы. На первом этапе методами оптической эмиссионной спектроскопии проводились измерения радиальных распределений температуры и электронной концентрации в плазме электродугового разряда в воздухе между композитными Cu-C и латунными электродами, а также медными электродами в потоке воздуха. На следующем этапе рассчитывались радиальные распределения электропроводности плазменной смеси путем решения уравнения энергетического баланса. Распределение электронной концентрации получено из электропроводности плазмы в допущении локального термодинамического равновесия. Запропонована комплексна методика дослідження плазми. На першому етапі методами оптичної емісійної спектроскопії проводились дослідження радіальних розподілів температури та електронної концентрації в плазмі електродугового розряду в повітрі між композитними Cu-C та латунними електродами, а також мідними електродами в потоці повітря. Наступним кроком розраховувались радіальні розподіли електро-провідності плазмової суміші шляхом розв’язку рівняння енергетичного балансу. Розподіл електронної концентрації отримали з електропровідності плазми в припущенні локальної термодинамічної рівноваги.